HUBUNGAN TINGKAT PENDIDIKAN DAN PENGGUNAAN LAHAN DENGAN TINGKAT PENDAPATAN PERTANIAN DI KECAMATAN JUMANTONO KABUPATEN KARANGANYAR TAHUN 2012 - Nidriyani, Hesti Kusuma (Pendidikan Geografi, 2013)
Hesti Kusuma Nindriyani. 2013. THE RELATIONSHIP OF EDUCATION LEVEL AND LANDUSE WITH FARMER INCOME LEVEL IN SUBDISTRICT OF JUMANTONO, DISTRICT OF KARANGANYAR. Skripsi. Surakarta: Faculty of Teacher Training and Education. Sebelas Maret University.Januari 2013. The aims of this research are to identify the relationship between (1). Education level and income level. (2). Landuse and income level. (3). Education level and landuse with level income. This research is using a correlational descriptive method. The population of research is all farmers in Subdistrict of Jumantono for about 18.786 people. The technique sampling is using proportional random sampling technique for about 165 people. The data collection technique of education level variable, landuse, and income level are using quisionaire and observation. The analyze technique is using correlation technique and double regretion analyzis. Based on the result of this research can be concluded that there is no relationship between formal education level and income level. (2) Landuse has not significant relationship with income level. (3) Education level and landuse have not significant relationship with income level.